PENGARUH KOMPETENSI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL MAHARADJA - Hendri Jopanda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2019)
This research aims to know the influence of competence, dicipline of work and environment of work on performance of employees on the Maharadja Hotel. Determining the research by using samples as much as 94 respondents and this research method by using multiple linear regression. This results show that the partially positive efffect and significant effect of competence against the performance of employees on the value of the Maharadja Hotel are thitung > ttabel 14.315 > 1.985 and significant value are 0.000 < 0.05 discipline of work influential positive effect and significantly to the performance of employees on the value of the Maharadja Hotel are thitung > ttabel 4.032 > 1.985 and significant are 0.000 < 0.05 and environment of work positive and significant effect on performance of employees on the value of the Maharadja Hotel are thitung > ttabel 5.007 > 1.985 and significant are 0.000 < 0.05 indicates that simultaneously while the competence, the discipline of work and environment of work on performance of employees on the value of the Maharadja Hotel are Fhitung > Ftabel > 106.533 > 2.70 with a significant level of 0.000 > 0.05.